(untitled) (Revista de Artes Marciales Asiáticas, 2012)
The present essay, with theoretic nature, assumes as an object of study the exhibition of the fundamental guidelines, on a didactic model, of the initiation to combat sports. For that, the contributions of several different authors were analyzed, who, from different points of view, consider that the initiation to combat sports does not imply a specific knowledge on any of the subjects that compose them, but their integrated and cross-curricular treatment. These alternative conceptions decreases the importance of the specific technical models, through the strengthening of the common elements of the combat sports, highlighting what is usually called “fighting knowledge”; that is, the capacity that allows the fighter to find solutions for the different situations that take place during a fight.